Double-Network Chitosan-Based Hydrogels with Improved Mechanical, Conductive, Antimicrobial, and Antibiofouling Properties - Rahela Carpa; Anca Farkas; Cristina Dobrota; Anca Butiuc-Keul (Gels, 2023)
In recent years, the antimicrobial activity of chitosan-based hydrogels has been at the forefront of research in wound healing and the prevention of medical device contamination. Anti-infective therapy is a serious challenge given the increasing prevalence of bacterial resistance to antibiotics as well as their ability to form biofilms. Unfortunately, hydrogel resistance and biocompatibility do not always meet the demands of biomedical applications. As a result, the development of double-network hydrogels could be a solution to these issues. This review discusses the most recent techniques for creating double-network chitosan-based hydrogels with improved structural and functional properties. The applications of these hydrogels are also discussed in terms of tissue recovery after injuries, wound infection prevention, and biofouling of medical devices and surfaces for pharmaceutical and medical applications.